2000
DOI: 10.1002/1097-0223(200009)20:9<746::aid-pd901>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Antepartum findings in fetal protein C deficiency

Abstract: A pregnancy with fetal homozygous protein C deficiency was complicated in the third trimester by fetal ventriculomegaly, intraorbital thrombosis and placental infarcts, which could be imaged by combined use of ultrasonography and MRI. Copyright © 2000 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This case report describes a newborn with purpura fulminans diagnosed with homozygous type II PC deficiency. Antepartum findings of the same patient have been reported previously (5). This report describes the therapy of the affected newborn and the prenatal diagnosis in a subsequent pregnancy.…”
supporting
confidence: 69%
“…This case report describes a newborn with purpura fulminans diagnosed with homozygous type II PC deficiency. Antepartum findings of the same patient have been reported previously (5). This report describes the therapy of the affected newborn and the prenatal diagnosis in a subsequent pregnancy.…”
supporting
confidence: 69%
“…Since 1998, of 20 published cases of homozygous protein C deficiency presenting with neonatal purpura fulminans worldwide, 2,6,7,9,[11][12][13][14][15][16][17][18] most have had a poor clinical outcome; 75% have complete blindness (n = 15), 33% have severe neurological impairment (n = 6), and 10% have died within the first few days of life (n = 2). Other major morbidities such as renal failure (n = 2), epilepsy (n = 1), and impaired growth and development (n = 4) have also been reported, with only 3 patients having escaped any major morbidity, because of very early and continuous treatment with protein C concentrate.…”
Section: Discussionmentioning
confidence: 99%
“…The parents of this patient were found to be heterozygous for PC deficiency, and the infant was homozygous. 8 A recent review of 27 Japanese patients receiving activated PC concentrate also retrospectively identified that three patients had fetal hydrocephalus, which preceded neonatal purpura fulminans. 7 In all reported cases, the diagnosis was made following the delivery through thrombophilia screening.…”
mentioning
confidence: 99%